Sintilimab, a PD-1 Inhibitor, Completely Reversed Rarely Refractory Hypofibrinogenemia in a Gastric Cancer Patient: A Case Report and Review of the Literature - Ma, Shuzhen; Dang, Qi; Yang, Yali; Liu, Yongliang; Sun, Yuping; Sun, Meili (Frontiers in Oncology, 2020)
While cancer is often related to hyperfibrinogenemia, it is rarely related to hypofibrinogenemia. Specifically, gastric cancer concomitant with unprovoked hypofibrinogenemia and the corresponding treatment approach have been rarely reported. We presented a case of gastric cancer in a 78-year-old Chinese woman in whom sudden, unprovoked refractory hypofibrinogenemia had been found during the whole brain radiotherapy (WBRT) despite stable clinical condition. Fibrinogen supplementation was not useful for controlling her level of fibrinogen. However, when she received sintilimab, an immunotherapy drug acting as programmed death receptor 1 (PD-1) inhibitor, to treat her gastric cancer, fibrinogen rose to the normal level. We also reviewed the literature to explore the causes of hypofibrinogenemia in tumor patients. This case suggests that we need to pay attention to tumor-related coagulation disorders, and monitoring coagulation indicators is essential. Treating primary disease by immunotherapy drugs may be an important method to improve the level of coagulation factors. This is the first report of sintilimab reversing a rare refractory hypofibrinogenemia in a patient with gastric cancer.